Mechanical recycling of bulk molding compound: a technical and environmental assessment (2024)
This study evaluates the technical and environmental feasibility of mechanically recycling post-industrial bulk molding compound (BMC) waste from the manufacturing of low voltage circuit breakers. Testing reveals that incorporating up to 10% recycled BMC as filler substitute maintains the required mechanical and electrical properties. A life cycle assessment shows that while replacing virgin fillers with recycled BMC has limited effects on the carbon footprint of the material, the overall product system benefits significantly by avoiding waste incineration. Moreover, optimized scenarios like maximizing recycled content and reducing transportations substantially reduce the environmental impacts. This study underscores the potential of circular production models to enhance sustainability in the thermoset composite industry